2017
DOI: 10.1002/mbo3.512
|View full text |Cite
|
Sign up to set email alerts
|

In vitro characteristics of Lactobacillus spp. strains isolated from the chicken digestive tract and their role in the inhibition of Campylobacter colonization

Abstract: Campylobacter jejuni/coli infections are the leading cause of bacterial diarrheal illnesses in humans. Many epidemiological studies indicate that improperly prepared meat from chickens that carry a high load of Campylobacter in their intestinal tracts is the key source of human infections. LAB, mainly members of the Lactococcus and Lactobacillus genera, increasingly have been tested as vehicles for the delivery of heterologous bacterial or viral antigens to animal mucosal immune systems. Thus, the objective of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 73 publications
1
34
0
3
Order By: Relevance
“…In previous studies, various species of probiotic bacteria such as L. reuteri [19,20], L. salivarius [19,21,16,22], Enterococcus faecium and Enterococcus durans [22]were isolated from chicken digestive tract. In the present study, four LAB isolates namely, IS3, IS4, IS6 and IS7 were identified based on sequence analysis of 16S rRNA gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, various species of probiotic bacteria such as L. reuteri [19,20], L. salivarius [19,21,16,22], Enterococcus faecium and Enterococcus durans [22]were isolated from chicken digestive tract. In the present study, four LAB isolates namely, IS3, IS4, IS6 and IS7 were identified based on sequence analysis of 16S rRNA gene.…”
Section: Discussionmentioning
confidence: 99%
“…The probiotics strains should have a property to grow and survive in the host digestive system as they exposed to a range of stressful conditions in the GIT which includes lower pH and high bile salt [26].The ability of probiotic strains to act as probiotics is also determined by the ability to survive in the low pH of the stomach and in the high concentration of bile salt of the gastrointestinal tract [19].…”
Section: Discussionmentioning
confidence: 99%
“…Duże zainteresowanie zyskało także stosowanie probiotyków jako środka zapobiegania lub zmniejszania częstości występowania infekcji Campylobacter u drobiu [82]. Obiecujące wyniki otrzymały zespoły Konkel i Jagusztyn-Krynickiej [47,65]. Zaobserwowali oni, że podanie kurczętom szczepów z rodzaju Lactobacillus, tj.…”
Section: Kampylobakterioza -Profilaktykaunclassified
“…Odmienne wyniki otrzymała grupa badawcza Jagusztyn-Krynickiej. Prototypy szczepionek powstałe w oparciu o liposomy zawierające immunogenne białko lub pęcherzyki błony zewnętrznej podane in ovo znacząco obniżały poziom kolonizacji jelit ślepych przez pałeczki Campylobacter [28,47].…”
Section: Droga Podania Antygenuunclassified
“…In theory, the use of silage as feed to organic broilers would combine all of these effects. In addition, it has been reported that provision of water inoculated with L. plantarum might decrease the level of C. jejuni colonisation in the bird's gut (Kobierecka et al 2017). Supplementing birds' drinking water with LAB in order to inhibit the growth and survival of C. jejuni, could be a promising strategy to reduce the load of C. jejuni in conventional broiler production.…”
Section: Introductionmentioning
confidence: 99%